Study on Strength Development and Microstructure of Cement-Solidified Peat Soil Containing Humic Acid of Dianchi Lake - Jing Cao; Siyang Huang; Wenlian Liu; Yue Gao; Yunfei Song; Songpo Li (Advances in Materials Science and Engineering)
The disposal of peat soil poses an increasingly difficult problem for actual engineering projects of Dianchi Lake area. This study obtains peat soil from seven areas around Dianchi Lake, and the content of humic acid (HA) in peat soil is between 2.36% and 28.13%. Then, this study simulates the peat soil by adding HA into the cohesive soil and uses cement to solidify it. The effect of cement and HA on the strength development of samples is examined by the unconfined compressive strength (UCS) test. Additionally, the microstructures of typical mixes are analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), and mercury intrusion porosimetry (MIP). The results showed that HA will significantly reduce the UCS of cement soil. The SEM, XRD, and MIP confirmed that cement hydration reaction increases with cement ratio. In addition to the cementitious soil particles, hydration products gradually fill the pores of the soil and effectively reduce the number of large-size (6000∼40,000 nm) pores in cement soil, which makes the soil particle framework stronger. When the cement ratio increases from 15% to 25%, the diffraction peak of CAH and CSH increases faster. Combined with the results of the UCS test, it could be proved that cement ratio greater than 20% weakens the influence of HA on the strength development of cement soil sample.